Longitudinal data from a school-based intervention - The ACORDA project (Datos longitudinales de un programa intervención en la escuela - proyecto ACORDA) - Aires, Luísa; Silva, Gustavo; Alves, Ana Inês; Medeiros, Ana Filipa; Nascimento, Henrique; Magalhães, Clarisse; Martins, Clarice; Pereira, Petronila Rocha; Santos-Silva, Alice; Belo, Luis; Mota, Jorge (Retos, 2015)
Abstract. The aim of this study was to analyse changes over 8-months of a multidisciplinary school-based intervention program (ACORDA-Project), in body fat, metabolic profile and physical activity (PA). 40 children [22 girls (55%), and 18 boys age=8.4±1.2] of 6 schools participated in a multidisciplinary program during a school year. Blood pressure (BP), physical activity (PA) by accelerometers, percentage of body fat (%BF) and of trunk fat (%TF) by DXA, and plasmatic total cholesterol (TC), triglycerides, HDL-cholesterol, LDL-cholesterol, insulin and glucose were taken at the baseline (Time point 1, TP1) and at the end of the intervention (Time point 2, TP2). General Linear Models (Repeated Measures Analysis of Covariance) was carried out comparing values at baseline vs. final evaluation, with adjustments for gender and age at baseline. Further adjustments were made to relative changes (increase%X) in height, weight, total PA through steps.day-1, sedentary (SEDPA), light (LIGPA) and moderate to vigorous (MVPA) intensities. Relative changes were calculated as: increase%X = (Xfinal – Xbaseline) / Xbaseline. Statistical significance was set at 5%. Eta squared (n2) was used as an indicator of effect size. There was a significant increase of LIGPA and MVPA, (P<0.05), and significant reduction in systolic blood pressure (P<0.05), but not in diastolic blood pressure. For TC and fasting glucose, significant reductions were also found P<0.05). No changes were observed for other traditional cardiovascular risk factors. The present study found that 8-months of multidisciplinary intervention provided a significant increase in PA levels and reduced cardiovascular risk factors in school children, highlighting the importance of this type of intervention through promotion of PA and the positive impact on children health. Resumen. El objetivo de este estudio fue analizar los cambios en la grasa corporal, el perfil metabólico y la actividad física (AF) en jóvenes escolares que han participado en un programa de intervención multidisciplinario (ACORDA-Project). 40 niños [22 niñas (55%), y 18 niños de edad = 8,4 ± 1,2] de 6 escuelas participaron en un programa multidisciplinario durante un año escolar. La presión arterial (PA), AF por acelerómetros, la porcentaje de grasa corporal (% GC) y de la grasa del tronco (% TF) por DXA, y el colesterol total plasmático (CT), triglicéridos, HDL-colesterol, LDL-colesterol, insulina, la glucosa se tomaron a la línea de base (punto de tiempo 1, TP1) y al final de la intervención (punto de tiempo 2, TP2). Modelos lineales generales (medidas repetidas análisis de covarianza) se utilizaran para la comparación de los valores al inicio del estudio vs. evaluación final, con ajustes para el género y la edad al inicio del estudio. Se hicieron nuevos ajustes a los cambios relativos (incremento%X) de altura, el peso, actividad física total (PA) a través de pasos por día, sedentaria (SEDPA), leve (LIGPA) y de moderada a (MVPA) intensidades vigorosas. Se calcularon los cambios relativos como: incremento%X = (xfinal - Xbaseline) / Xbaseline. La significación estadística se fijó en 5%. Eta cuadrado (n2) se usó como un indicador del tamaño del efecto. Se observó un aumento significativo de LIGPA y MVPA, (P <0.05) y una reducción significativa de la presión arterial sistólica (p <0,05), pero no en la presión arterial diastólica. Para el CT y la glucosa en ayunas, también se encontraron reducciones significativas (P<0.05). No se observaron cambios en otros factores de riesgo cardiovascular tradicionales. El presente estudio encontró que 8-meses de intervención multidisciplinaria proporcionaron un aumento significativo en los niveles de AF y reducción de factores de riesgo cardiovascular en niños en edad escolar. Se destaca la importancia de este tipo de intervención a través de la promoción de la AF y el impacto positivo en la salud de los niños.